2023
DOI: 10.1111/cid.13247
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ridge preservation in sockets with severe periodontal destruction using autogenous partially demineralized dentin matrix: A randomized controlled clinical trial

Abstract: BackgroundThe preservation and reconstruction of alveolar ridge volume in extraction sockets of molars affected by severe periodontitis is a critical challenge that requires clinical attention.PurposeThis randomized controlled clinical trial was designed to evaluate the efficiency of autogenous partially demineralized dentin matrix (APDDM) for alveolar ridge preservation (ARP) in severely periodontally compromised sockets compared to spontaneous healing (SH) on radiographic and histomorphometric outcomes.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…Of the 6 included articles, 2 articles [ 37 , 38 ] originated from the same research group and reported different outcomes separately in the 2 articles for the same cohort, resulting in a total number of 5 included studies in this review. Among the 6 included articles, 2 were RCT [ 2 , 39 ] and 4 were non-RCT [ 33 , 37 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 6 included articles, 2 articles [ 37 , 38 ] originated from the same research group and reported different outcomes separately in the 2 articles for the same cohort, resulting in a total number of 5 included studies in this review. Among the 6 included articles, 2 were RCT [ 2 , 39 ] and 4 were non-RCT [ 33 , 37 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included were between 2010 and 2023. All studies were conducted in China [ 33 , 37 , 38 , 39 , 40 ] except for one that was conducted in Europe [ 2 ]. A total of 130 participants with 135 extraction sites were included, taking note that the 3 articles were under the same clinical trial registration [ 37 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations